2021
DOI: 10.1038/s41598-021-95900-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of macrolides in management of patients with mild COVID-19

Abstract: Evidence on the efficacy of adding macrolides (azithromycin or clarithromycin) to the treatment regimen for COVID-19 is limited. We testify whether adding azithromycin or clarithromycin to a standard of care regimen was superior to standard of supportive care alone in patients with mild COVID-19.This randomized trial included three groups of patients with COVID-19. The azithromycin group included, 107 patients who received azithromycin 500 mg/24 h for 7 days, the clarithromycin group included 99 patients who r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The findings from the large RECOVERY trial confirmed several previous studies that found modest or no benefit in azithromycin use in patients admitted to hospital with COVID-19 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The findings from the large RECOVERY trial confirmed several previous studies that found modest or no benefit in azithromycin use in patients admitted to hospital with COVID-19 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
“…Two-hundred-forty-five studies were excluded for not reporting data on antibiotic use in COVID-19 patients. From the remaining 118 studies, 36 studies were included in this systematic review ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most useful antimicrobials against H. pylori [15]. It is recently integrated in the treatment protocol of COVID-19 [16,17]. LAN is a PPI that reduces gastric acidity [18].…”
Section: Introductionmentioning
confidence: 99%